Polymer nanocomposites based on silylated-montmorillonite: A review. (October 2018) - Bee, Soo-Ling; Abdullah, M.A.A.; Bee, Soo-Tueen; Sin, Lee Tin; Rahmat, A.R.
Graphical abstract: Abstract: Recently, polymer nanocomposite reinforced with well-dispersed layered silicate, typically montmorillonite have received much attention in both academic and industrial research due to their promising and peculiar features compared to traditional composite materials. However, owing to the incompatibility arising from the hydrophilic characteristics of the pristine montmorillonite in nature, surface modification of montmorillonite becomes indispensable in order to enhance its interfacial interaction with the organic phase. Herein, a type of covalent organic functionalization approach is reviewed, namely silylation to coat silane coupling agents on the clay, considered to be a salient aspect to improve nanofiller dispersion in the polymeric matrix, besides the processing method and nature of the polymer. Consequently, emphasis is placed on possible factors that affect the degree of surface modification during silylation, such as the silane configuration, reaction conditions and the nature of the solvent system. Moreover, the effect of the impregnation of silylated-fillers in various macromolecular matrices is summarized and compiled based on recent collected literature where their processing, morphologies, properties and future prospects are specifically detailed and discussed in this review.